Hermeneutical Phenomenology of Corporate Financial Failure in Ungaran District, Bawen, Semarang Regency, Central Java - Apollo, Apollo (Green Publisher, 2023)
This study uses qualitative methods on companies in Ungaran District, Bawen, Semarang Regency, Central Java with negative equity categories for 2 (two) consecutive years. A company experiencing negative equity or a condition of financial distress is a company's financial position in an unhealthy condition or crisis. Financial distress is a symbol of bankruptcy in accounting. This means that it is not yet or is not legally bankrupt. This research method uses phenomenology and hermeneutics in corporate financial failures to understand the meaning of the experiences of company managers and owners, companies, inter-subjective activities in the hermeneutic process between researchers and people who experience them. Semi-structured and ethnographic interviews, lived experience (Erlebnis), were conducted with eight (8) company research unit objects in Ungaran District, Bawen Regency, Semarang Regency, conducted for approximately 6, consecutive months. The results of this research understand (Verstehen) on the hermeneutic phenomenology of corporate financial failure caused by three things: (1) prejudice, and failure of Gadamer horizon fusion; (2) failure to